Wind tunnel 2-DOF hybrid/HIL tests on the OC5 floating offshore wind turbine - Bayati, Ilmas; Belloli, Marco; Facchinetti, Alan (Volume 10: Ocean Renewable Energy, 2017)
This paper presents the numerical and experimental implementation of a 2 degrees-of-freedom (DoF) setup for simulating the surge and pitch motion of OC5 semi submersible floating offshore wind turbine, through the "hardware-in-the-loop" (HIL) approach during wind tunnel tests. This approach is hybrid since a real-time combination of computations and measurements are carried out during the experiments. This allows to separate the model tests of floating wind turbines into wave/ocean basin and wind tunnel tests, as it is currently done within the H2020/LIFES50+ project respectively at Marintek (Norway) and Politecnico di Milano (Italy), with the possibility of exploiting the advantages of each facility and overcoming the scaling issues and conflicts (e.g. Froude-Reynolds) that are emphasized when it comes to testing both wind and wave in a single test facility. In this paper the modelling approach and experimental implementation are presented, with a special focus on signals and data handling in the real-time HIL control system aimed at minimizing the effect of model/full scale discrepancies. Results are shown for free decays, regular and irregular sea states, showing promising results for the next 6-DoF system being finalized.